Brief Research Report: Effect of Triiodothyronine on Hepatic Growth Hormone Receptor Expression in Primary Bovine Hepatocytes - Stiensmeier, Vera; Schmicke, Marion (Frontiers in Veterinary Science, 2022)
In previous studies, triiodothyronine (T3) was found to be lower in cows with ketosis and an effect of T3 on Growth Hormone Receptor (GHR) expression is described, e. g., in a human hepatoma cell line. Therefore, this study aimed to test whether T3 affects GHR messenger RNA (mRNA) expression in a well-established bovine hepatocyte model. Hepatocytes were kept in a sandwich culture and stimulated for 6 days with constant (10 μg/ml) or decreasing (from 10 to 5 μg/ml) T3 concentrations, and GHR, as well as IGF-1 mRNA expression, was measured using real-time polymerase chain reaction (RT-PCR). We could confirm in vitro that T3 has a stimulatory effect on GHR1A mRNA expression.